Blood Inflammatory Cytokines as Predictors of Depression in Patients With Glioma - Li, Huayu; Shi, Xiaohan; Yang, Fan; Zhang, Xinrui; Li, Feng (Frontiers in Psychiatry, 2022)
Background: Depression commonly develops as a comorbid disorder related to glioma, which affects the patients' physical function and prognosis. Circulating inflammatory cytokines are potential predictors of depression in disparate cancers. However, little research has specifically investigated this aspect within the context Study Objectives: To investigate the occurrence of depression in glioma patients and draw a comparison of the ability to predict it through diverse inflammatory cytokines. Methods: A total of 203 patients with stage Ⅰ-Ⅳ glioma were enrolled in this study. Depression was evaluated according to the Hamilton Depression Scale, and the plasma inflammatory cytokines levels were simultaneously measured. We performed the receiver operating characteristic (ROC) analysis to confirm the abilities of identified inflammatory cytokines to predict depression. Results: Among the 203 patients with glioma,135 (66.5%) showed obvious depressive symptoms. Proinflammatory cytokines IL-6 (AUC = 0.76) and TNF-α (AUC = 0.75) showed good performance in accurately predicting depression in glioma patients. These inflammatory cytokines indicated great potential to be depression biomarkers regardless of the patients’ disparate treatment experience. Conclusions: With their relatively simple and time saving measurement procedures, inflammatory cytokines should be seriously considered as effective clinical screening and diagnostic tools as well as potential biomarkers for depression in glioma patients.